Characterization and Comparison of the CPK Gene Family in the Apple (Malus × domestica) and Other Rosaceae Species and Its Response to Alternaria alternata Infection. - Menghan Wei; Sanhong Wang; Hui Dong; Binhua Cai; Jianmin Tao (PLoS ONE, 2016)
As one of the Ca2+ sensors, calcium-dependent protein kinase (CPK) plays vital roles in immune and stress signaling, growth and development, and hormone responses, etc. Recently, the whole genome of apple (Malus × domestica), pear (Pyrus communis), peach (Prunus persica), plum (Prunus mume) and strawberry (Fragaria vesca) in Rosaceae family has been fully sequenced. However, little is known about the CPK gene family in these Rosaceae species. In this study, 123 CPK genes were identified from five Rosaceae species, including 37 apple CPKs, 37 pear CPKs, 17 peach CPKs, 16 strawberry CPKs, and 16 plum CPKs. Based on the phylogenetic tree topology and structural characteristics, we divided the CPK gene family into 4 distinct subfamilies: Group I, II, III, and IV. Whole-genome duplication (WGD) or segmental duplication played vital roles in the expansion of the CPK in these Rosaceae species. Most of segmental duplication pairs in peach and plum may have arisen from the γ triplication (~140 million years ago [MYA]), while in apple genome, many duplicated genes may have been derived from a recent WGD (30~45 MYA). Purifying selection also played a critical role in the function evolution of CPK family genes. Expression of apple CPK genes in response to apple pathotype of Alternaria alternata was verified by analysis of quantitative real-time RT-PCR (qPCR). Expression data demonstrated that CPK genes in apple might have evolved independently in different biological contexts. The analysis of evolution history and expression profile laid a foundation for further examining the function and complexity of the CPK gene family in Rosaceae.